In vivo evaluation of the regenerative capability of glycylglycine ethyl ester-substituted polyphosphazene and poly (lactic-co-glycolic acid) blends: A rabbit critical-sized bone defect model - Ogueri, Kenneth S. (ACS Biomater Sci Eng, 2021)
In an effort to understand the biological capability of polyphosphazene-based polymers, three-dimensional (3D) biomimetic bone scaffolds were fabricated using blends of poly[(glycine ethylglycinato)(75)(phenylphenoxy)(25)]phosphazene (PNGEGPhPh) and poly(lactic-co-glycolic acid) (PLGA), and an in vivo evaluation was performed in a rabbit critical-sized bone defect model. The matrices constructed from PNGEGPhPh-PLGA blends were surgically implanted into 15mm critical-sized radial defects of the rabbits as structural templates for bone tissue regeneration. PLGA, which is the most commonly used synthetic bone graft substitute, was used as a control in this study. Radiological and histological analyses demonstrated that PNGEGPhPh-PLGA blends exhibited favorable in vivo biocompatibility and osteoconductivity as the newly designed matrices allowed new bone formation to occur without adverse immunoreactions. X-ray images of the blends showed higher levels of radiodensity than that of the pristine PLGA, indicating higher rates of new bone formation and regeneration. Micro-computed tomography instrument (micro-CT) quantification revealed that new bone volume fractions were significantly higher for the PNGEGPhPh-PLGA blends than for the PLGA controls after 4 weeks. The new bone volume increased linearly with increasing time points, with the new tissues observed throughout the defect area for the blend and only at the implant site’s extremes for the PLGA control. Histologically, the polyphosphazene system appeared to show tissue responses and bone ingrowths superior to that of PLGA. By the end of the study, the defects with PNGEGPhPh-PLGA scaffolds exhibited evidence of effective bone tissue-ingrowth and minimal inflammatory responses. Thus, polyphosphazene-containing biomaterials have excellent translational potential for use in bone regenerative engineering applications.